Inovasi Kegiatan Literasi FTBM Jawa Barat Dan TBM Jatmika Bandung Dalam Menjaga Energi Literasi Masyarakat Jawa Barat Di Masa Pandemi - Fadhilah Luthfi Afifatunnisa; Sukaesih Sukaesih; Evi Nursanti Rukmana; Asep Saeful Rohman (Ikatan Pustakawan Indonesia, 2021)
This study aims to identify and describe the innovation activities and literacy movements carried out by the West Java Community Library Forum (FTBM) and the Jatmika Bandung Community Library (TBM) in the midst of the Covid-19 pandemic. The method used in this research is descriptive method with a qualitative approach and data collection techniques through interviews, observation, documentation and literature study. This study aims to obtain an empirical picture of creative innovations created by FTBM in the West Java region, especially at TBM Jatmika Bandung, in order to remain productive in providing collection services and activities aimed at improving the culture of reading or community literacy during the pandemic. The results of the study show that each FTBM and TBM in the West Java region collaborate with each other and play an active role in creating innovative literacy activities and movements virtually or online without reducing the spirit of community literacy energy and literacy activists in West Java. FTBM and TBM in West Java created a new strategy, namely by transforming all of their activities into alternative digital media to encourage literacy activities with new faces that are more fun. In addition, this strategy is also useful in providing convenience for the community in meeting literacy needs wherever and whenever. Thus, TBM can continue to play a role as a means to increase reading interest and literacy skills of the people of West Java even in the midst of a pandemic.